Last Year at Betty and Bob's: A Novelty - Doruff, Sher (punctum books, 2018)
Last Year at Betty and Bob's: A Novelty is the first in a series of novellas emerging from a writing practice that taps the cusp of consciousness between dreaming and waking. A storyline, or genealogy, tinted a shade of RGB blue, is fashioned by thinking through the felt unthought of this between space. A fabulation, an anarchive of what passes through. Lucid dreaming of this type is rife with allusions to conceptual and material goings-on, manifesting in awkward imaginaries. The dream personas are rendered as complex character amalgams with nomadic ages, sexes, genders and phenotypes. Occurrences of lived "fact" elide with a hallucinatory real as speculation. In A Novelty, Bette B, an ageing quasi-academic artist researcher, and BØB, attuned urban rodent, are palindromic variants of a generic cast of Betty's and Bob's. The happenstance of their meeting on the super slick POMOC (PostOffice MotionCorridor) affects a trans-special contagion. These are the facts of the matter. The matters that come to concern both B's are more slippery and elusive.